Empathetic Communication and Social Management Strategies in Increasing Awareness for Orphans - Dila Erlianti; Lilis Wahyuni; Yesi Mala Sari; Reza Syahputra Alfandi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Stunting remains a chronic nutritional issue in Indonesia, particularly among children under five, affecting cognitive development, physical growth, and the productivity of the younger generation (Ministry of Health, 2023). This community service aims to enhance the role of public administration in promoting policies and programs to combat stunting through education, training, and direct assistance. Activities were conducted in coordination with government officials, health cadres, and local leaders, utilizing local media to raise awareness about nutrition. The results showed a significant increase in community knowledge about stunting and balanced nutrition, with active participation from both officials and residents in the reduction programs. This approach underscores the importance of public administration in fostering sustainable community health initiatives. In parallel, this program also focuses on enhancing community care for orphans through strategies like empathetic communication and social management. Using a participatory and qualitative approach, both the community and orphans were involved in every stage of the activity. The results indicated improved social interactions between the community and orphans, with the children showing positive emotional responses such as comfort and acceptance. The community demonstrated increased participation and responsibility. By integrating empathetic communication with social management, the program successfully enhanced the emotional well-being of orphans and strengthened community solidarity, suggesting a sustainable model for future social care initiatives.